Role of C-tactile fibers in pain modulation: animal and human perspectives. (February 2022) - Larsson, Max; Nagi, Saad S
Highlights: Human and animal studies suggest a possible role for C-LTMRs in allodynia. Activation of C-LTMRs may also alleviate pain in some contexts. Diverse synaptic and non-synaptic C-LTMR signals may bidirectionally modulate pain. Abstract : C-tactile (CT) fibers, a population of unmyelinated (C) fibers that respond particularly well to gentle stroking, are widely believed to subserve affective touch. However, these fibers (termed C low-threshold mechanoreceptors (C-LTMRs) in non-human mammals) have also been proposed to be involved in the modulation of pain. Intriguingly, functional evidence from both human and animal studies indicates that CT/C-LTMR fibers can both contribute to allodynia as well as mediate pain inhibition. In the spinal cord, C-LTMR fibers form glomerular synaptic arrangements, providing input to several populations of interneurons within the nociceptive circuitry. Thus, the CT/C-LTMR system conveys signals that are subject to intricate processing in the spinal cord and is well-situated within spinal sensory pathways to enable the modulation of pain.